Razkrivanje osebnosti in delovanja publicista, smučarja in gornika Rudolfa Badjure - Berčič, Herman (Šport (Ljubljana), 2014)
The symposium on Rudolf Badjura, which was organised in the middle of March (2014) by the Slovenian Association of Mountain Soldiers and the Multinational Centre of Excellence for Mountain Warfare of the Slovenian Armed Forces in the Defence Training Centre of the Ministry of Defence in Poljče near Begunje in the Gorenjska region, revealed a series of interesting facts and also new findings. The participating authors shed light from different angles on the life and work of Rudolf Badjura. Eventually, it was not only reasonable but also justified and necessary to put this extremely interesting Slovenian, patriot, military officer, hiker, mountaineer, skier, teacher and author of the first Slovenian mountaineering and tourist guides in the spotlight because of his many merits for the Slovenian nation in terms of its survival and development.
Keywords: Badjura, Rudolf, 1881-1963; gorništvo; hiking; journalism; mountaineering; planinstvo; pohodništvo; publicistika; recreational mountaineering; skiing; smučanje; sport; sport tourism; šport; športni turizem; tourist literature; turistično slovstvo